Grasshopper and Butterfly - Piers, Helen (New York McGraw-Hill, 1975)
Grasshopper sets out to find Butterfly a warm place for the winter - a wide-ranging quest with a poignant and reassuring outcome.
1
Keywords: English fiction; Children's literature, English